The G-Protein-Coupled Chemoattractant Receptor Fpr2 Exacerbates High Glucose-Mediated Proinflammatory Responses of Müller Glial Cells - Yu, Ying; Bao, Zhiyao; Wang, Xiaofei; Gong, Wanghua; Chen, Hui; Guan, Huaijin; Le, Yingying; Su, Shaobo; Chen, Keqiang; Wang, Ji Ming (Frontiers in Immunology, 2017)
In proliferative diabetic retinopathy (PDR), activated Müller glial cells (MGCs) exhibit increased motility and a fibroblast-like proliferation phenotype that contribute to the formation of fibrovascular membrane. In this study, we investigated the capacity of high glucose (HG) to regulate the expression of cell surface receptors that may participate in the proinflammatory responses of MGCs. We found that MGCs express a G-protein coupled chemoattractant receptor formyl peptide receptor 2 (Fpr2) and fibroblast growth factor receptor 1 (FGFR1), which mediated MGC migration and proliferation in response to corresponding ligands. HG upregulated Fpr2 through an NF-κB pathway in MGCs, increased the activation of MAPKs coupled to Fpr2 and FGFR1, which also further enhanced the production of vascular endothelial growth factor by MGCs in the presence of HG. In vivo, Fpr2 was more highly expressed by retina MGCs of diabetic mice and the human counterpart FPR2 was detected in the retina MGCs in fibrovascular membrane of PDR patients. To support the potential pathological relevance of Fpr2, an endogenous Fpr2 agonist cathelin-related antimicrobial peptide was detected in mouse MGCs and the retina, which was upregulated by HG. These results suggest that Fpr2, together with FGFR1, may actively participate in the pathogenesis of PDR thus may be considered as one of the potential therapeutic targets.